Let $k_1=2$ and $k_2=3$ and $\mu_1=1$ and $\mu_2=3$. I would like to evaluate the following sum \begin{align} S=&\sum_{i=1}^{2} \sum_{j=1}^{k_i}\\ \times& \sum_{\begin{matrix} n_1+n_2=k_i-j\\ n_i=0 \end{matrix}}^{}\prod_{\begin{matrix} l=1\\ l\neq i \end{matrix}}^{2} \binom{k_l+n_l-1}{n_l}\frac {u_l^{k_l}} {(\mu_l-\mu_i)^{k_l+n_l}} \end{align} My question is how we get $n_1$ and $n_2$ and evaluate the above sum? What is the meaning of this summation and it name where only $k_j$ and $\mu_j$ are known? $$ \sum_{ \begin{matrix} n_1+n_2+\cdots n_n=k_i-j\\ n_i=0 \end{matrix}}^{} $$ Does any one have work with this sum or have some examples about it? This is independent part, I found the same sum in Leibniz formula which is the derivation of product of $m$ functions given by $$ (v_1v_2v_3\cdots v_m)^n=\sum_{ \begin{matrix} t_1+t_2+\cdots t_m=n\\ t_1,t_2,\cdots t_m\geq0 \end{matrix}}^{}\frac {n!} {t_1!t_2!\cdots t_m!}v_1^{(t_1)}v_2^{(t_2)}\cdots v_m^{(t_m)} $$ Just how we can found all $t_i$ or $n_i$ and the sum?


We have the pleasant situation that the index range of $i$ is small, namely $i\in\{1,2\}$. So, expanding the outer sum gives two terms only. The product with index $l$ is in fact a single factor, since $l$ is also either $1$ or $2$, but complementary to $i$.

We obtain \begin{align*} \color{blue}{\sum_{i=1}^2}&\color{blue}{\sum_{j=1}^{k_i}\sum_{{n_1+n_2=k_i-j}\atop{n_i=0}}\prod_{{l=1}\atop{l\ne i}}^2 \binom{k_l+n_l-1}{n_l}\frac{u_l^{k_l}}{(\mu_l-\mu_i)^{k_l+n_l}}}\\ &=\sum_{j=1}^{k_1}\sum_{{n_1+n_2=k_1-j}\atop{n_1= 0}}\prod_{{l=1}\atop{l\ne 1}}^2 \binom{k_l+n_l-1}{n_l}\frac{u_l^{k_l}}{(\mu_l-\mu_1)^{k_l+n_l}}\tag{1}\\ &\qquad+\sum_{j=1}^{k_2}\sum_{{n_1+n_2=k_2-j}\atop{n_2= 0}}\prod_{{l=1}\atop{l\ne 2}}^2 \binom{k_l+n_l-1}{n_l}\frac{u_l^{k_l}}{(\mu_l-\mu_2)^{k_l+n_l}}\\ &=\sum_{j=1}^{k_1}\sum_{n_2=k_1-j} \binom{k_2+n_2-1}{n_2}\frac{u_2^{k_2}}{(\mu_2-\mu_1)^{k_2+n_2}}\tag{2}\\ &\qquad+\sum_{j=1}^{k_2}\sum_{n_1=k_2-j} \binom{k_1+n_1-1}{n_1}\frac{u_1^{k_1}}{(\mu_1-\mu_2)^{k_1+n_1}}\\ &=\sum_{j=1}^{k_1}\binom{k_1+k_2-j-1}{k_1-j}\frac{u_2^{k_2}}{(\mu_2-\mu_1)^{k_1+k_2-j}}\tag{3}\\ &\qquad+\sum_{j=1}^{k_2}\binom{k_1+k_2-j-1}{k_2-j}\frac{u_1^{k_1}}{(\mu_1-\mu_2)^{k_1+k_2-j}}\\ &=\sum_{j=1}^{2}\binom{4-j}{2-j}\frac{u_2^3}{2^{5-j}}+\sum_{j=1}^{3}\binom{4-j}{3-j}\frac{u_1^2}{(-2)^{5-j}}\tag{4}\\ &=\left(\binom{3}{1}\frac{1}{2^4}+\binom{2}{0}\frac{1}{2^3}\right)u_2^3\\ &\qquad+\left(\binom{3}{2}\frac{1}{(-2)^4}+\binom{2}{1}\frac{1}{(-2)^3}+\binom{1}{0}\frac{1}{(-2)^2}\right)u_1^2\tag{5}\\ &\,\,\color{blue}{=\frac{1}{16}\left(u_1^2+5u_2^3\right)} \end{align*}


  • In (1) we expand the outer sum which gives two terms with $i=1$ and $i=2$.

  • In (2) we substitute $l=2$ in the first term and $l=1$ in the second term. We also substitute $n_1=0$ in the first term and $n_2=0$ in the second term.

  • In (3) we substitute $n_2$ in the first term and $n_1$ in the second term.

  • In (4) we set the values with $k_1,k_2,\mu_1$ and $\mu_2$.

  • In (5) we expand the sums.

Note: The sum with index range \begin{align*} \sum_{{t_1+t_2+\cdots+t_m=n}\atop{t_1,t_2,\ldots,t_m\geq 0}} \end{align*} has different character than the sum above, since here we sum over all $m$-tupel $(t_1,t_2,\ldots,t_m)$ with non-negative integral components which sum up to $n$. For small $n$ and $m$ all valid $m$-tupel can be determined manually. Greater values of $m$ or $n$ will usually need assistence by a computer.

  • $\begingroup$ Ok prof, thank you so much. $\endgroup$ – Monir Sep 18 '18 at 23:05
  • $\begingroup$ @Monir: You're welcome. $\endgroup$ – Markus Scheuer Sep 19 '18 at 6:16

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.